BRITISH CHAMBER OF COMMERCE AND THE COMPETITION AGAINST GERMAN BUSINESS ACTIVITIES IN THE NETHERLANDS INDIES - Mulyasari, Prima Nurahmi (History Department, Semarang State University and Historian Society of Indonesia, 2018)
After World War I German business activities in Netherlands Indies became a seriously earnest threat according to British Chamber of Commerce because the British firms were anxious that this would menace their market in the Dutch colony. In their publications during 1920-1923, the features and editorial comments of Netherlands Indies Review frequently exposed the rivalry between Britain and Germany. The approach of this paper is business history that narrates to what extent the commercial competition happened between the two industrial countries as it was shown by the Netherlands Indies Review, a monthly journal issued by the British Chamber of Commerce. Eventually, the British Chamber of Commerce concluded that GermanyÃ¢â‚¬â„¢s efforts to strengthen her commercial position in Netherlands Indies after the Great War was not meeting with any success.Ã‚Â Pasca Perang Dunia I aktivitas-aktivitas bisnis Jerman di Hindia Belanda menjadi ancaman serius menurut Kamar Dagang Inggris dikarenakan Inggris cemas bahwa mereka akan mengancam distribusi produk-produk industri Inggris di koloni Belanda tersebut. Dalam publikasi Netherlands Indies Review pada kurun waktu 1920-1923 berbagai berita editorial yang dimuat oleh jurnal milik Kamar Dagang Inggris ini sering mengulas persaingan bisnis yang sengit antara Inggris dan Jerman. Pendekatan dalam makalah ini adalah sejarah bisnis yang bertujuan untuk menarasikan sejauhmana persaingan bisnis antara kedua negara industri ini sebagaimana dipublikasikan oleh Netherlands Indies Reviews. Kamar dagang Inggris kemudian menyimpulkan bahwa upaya Jerman untuk memperkuat posisi komersialnya di Hindia Belanda setelah Perang Dunia I tidak berjalan dengan sukses.Ã‚Â